2001
DOI: 10.1103/physrevlett.87.026101
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical Properties and Formation Mechanisms of a Wire of Single Gold Atoms

Abstract: A scanning tunneling microscope (STM) supplemented with a force sensor is used to study the mechanical properties of a novel metallic nanostructure: a freely suspended chain of single gold atoms. We find that the bond strength of the nanowire is about twice that of a bulk metallic bond. We perform ab initio calculations of the force at chain fracture and compare quantitatively with experimental measurements. The observed mechanical failure and nanoelastic processes involved during atomic wire fabrication are i… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

93
402
4
4

Year Published

2003
2003
2017
2017

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 398 publications
(503 citation statements)
references
References 24 publications
93
402
4
4
Order By: Relevance
“…The conductance as a function of the Au atom chain length in individual pulls shows steps which are of the order of 0.1 G 0 , i.e., remarkably larger than the oscillations in our results for the Au chains with constant interatomic distances. Similar steps were recorded earlier by Rubio-Bollinger et al 22 Furthermore, Smit et al concluded that the maxima ͑minima͒ in the conductance correspond to an odd ͑even͒ number of atoms in the chain. This is also in contrast to our results in Fig.…”
Section: Electron Transport Through Monovalent Atomic Wiressupporting
confidence: 67%
“…The conductance as a function of the Au atom chain length in individual pulls shows steps which are of the order of 0.1 G 0 , i.e., remarkably larger than the oscillations in our results for the Au chains with constant interatomic distances. Similar steps were recorded earlier by Rubio-Bollinger et al 22 Furthermore, Smit et al concluded that the maxima ͑minima͒ in the conductance correspond to an odd ͑even͒ number of atoms in the chain. This is also in contrast to our results in Fig.…”
Section: Electron Transport Through Monovalent Atomic Wiressupporting
confidence: 67%
“…The way ∆t 5 is obtained is similar to that used to measure experimental plateau lengths distributions [22]. However, we have found that this quantity does not reflect the actual maximum length of the icosahedral nanowires L m p .…”
Section: Resultsmentioning
confidence: 72%
“…However, we note that the resulting thermal stresses can be of similar order of magnitude as the tensile film stress resulting in large uncertainties in this estimation. Nevertheless, this stiffness is clearly below the one of Au-Au contacts (~1.5 N/m) 6 and therefore not suitable for achieving a controlled breaking process. Instead it supports our observation of abrupt breaking from large contacts (GEL > 10 G0) to tunnelling during retraction of the tip.…”
Section: Stiffness Estimation Of the Mems Devicementioning
confidence: 89%